Rancang Bangun Alat Pemotong Daging Sapi Untuk Sate - , Moehamad Helmy Fauzi; Arifin; Jojo Sumarjo (Jurnal Serambi Engineering, 2025)
This research focuses on the design and construction of a beef cutting tool specifically aimed at improving the efficiency and productivity of satay vendors. The tool utilises a 1/4 hp electric motor to drive a 10" circular blade, allowing the meat to be cut quickly and evenly. Key materials used in the construction of this tool include SS400 steel for the frame structure and stainless steel for the base, ensuring optimum strength and durability. Test results indicate that the tool significantly streamlines and speeds up the meat cutting process compared to current manual methods, thereby increasing the productivity of micro, small and medium enterprises (MSMEs). Future development proposals include improvements to ergonomics and safety features, as well as initiatives to reduce vibration for improved user comfort.